2013
DOI: 10.1061/(asce)gm.1943-5622.0000207
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Design Parameters for Braced Excavation: Numerical Study

Abstract: This paper discusses the development of a numerical model for a braced excavation to estimate the various design parameters that significantly influence the excavation's behavior. The results of the numerical model were compared with those of a reported case study of a braced excavation in sand, and close agreement between the results was observed. The developed model is used for parametric study to show the influence of different design parameters, such as strut stiffness, wall thickness, strut arrangement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The optimum values of the design parameters i.e. wall thickness, embedment depth of the wall, the stiffness of the struts and the depths of the struts below ground level have been obtained under static condition and a design guideline of braced excavation have been proposed under static condition [7]. However, very few studies have been done for analyzing the behavior of such type of excavation under seismic condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum values of the design parameters i.e. wall thickness, embedment depth of the wall, the stiffness of the struts and the depths of the struts below ground level have been obtained under static condition and a design guideline of braced excavation have been proposed under static condition [7]. However, very few studies have been done for analyzing the behavior of such type of excavation under seismic condition.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the work [7], the depth of excavation (D e ), depth of embedment of the wall below the final excavation level (D b ), thickness of the wall (t wall ) and the stiffness of the struts are taken as 10m, 8m, 0.6m and 5x10 5 kN/m/m, respectively. The width of excavation is taken as 10m.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have the disadvantages of poor workability and high construction cost, and require an additional process for their installation because of their narrow spacing (Kim et al, 2005). In addition, bracing is a component that may act as an obstacle to deep excavation work and the construction of the structure (Choudhury et al, 2013). Bracing can also increase construction costs because it requires more steel.…”
Section: Strut Support System Of a Retaining Wallmentioning
confidence: 99%
“…The parametric study was used to derive a design guideline to optimize the side support system. It was observed that, for a particular wall thickness and strut stiffness, different strut arrangements produced different results for maximum strut force, maximum moment, maximum horizontal wall displacement, and maximum vertical ground surface displacement [2].…”
Section: Introductionmentioning
confidence: 99%